Serum soluble receptor for advanced glycation end products (sRAGE) is independently associated with cigarette smoking in non-diabetic healthy subjects - Biswas, Subrata Kumar; Mudi, Sonchita R; Mollah, Forhadul H; Bierhaus, Angelika; Arslan, M Iqbal (Diabetes & vascular disease research, 2013)
This study was designed to explore the relationship between serum levels of soluble receptor for advanced glycation end products (sRAGE) and cigarette smoking in non-diabetic healthy subjects. A total of 98 non-diabetic, otherwise healthy male subjects were recruited. A fasting blood sample and medical history including detail history of cigarette smoking was collected. The serum sRAGE levels were found significantly higher (p=0.002) in cigarette smokers (1475±422 pg/ml, n=45) compared with non-smokers (1165±350 pg/ml, n=53). Moreover, among the cigarette smokers, serum sRAGE levels were found significantly correlated with number of cigarettes smoked per day (r=0.60, p<0.001). In bivariate analysis in the total population, sRAGE positively correlated with smoking habit (r=0.37, p=0.002) and negatively correlated with systolic (r=-0.32, p=0.01) and diastolic blood pressure (r=-0.36, p=0.003). However, in stepwise multivariate linear regression model, sRAGE showed a significant independent association with smoking habit (b=0.32, p=0.007, R2=0.23). In conclusion, this study for the first time shows a significant elevation of serum sRAGE in cigarette smokers compared with non-smokers, a strong correlation between sRAGE and number of cigarettes smoked per day and an independent association of sRAGE with smoking habit in non-diabetic healthy subjects.
Gesehen am 26.11.2020